Platelets and platelet extracellular vesicles in drug delivery therapy: A review of the current status and future prospects - Dai, Zhanqiu; Zhao, Tingxiao; Song, Nan; Pan, Kaifeng; Yang, Yang; Zhu, Xunbin; Chen, Pengfei; Zhang, Jun; Xia, Chen (Frontiers in Pharmacology, 2022)
Platelets are blood cells that are primarily produced by the shedding of megakaryocytes in the bone marrow. Platelets participate in a variety of physiological and pathological processes in vivo, including hemostasis, thrombosis, immune-inflammation, tumor progression, and metastasis. Platelets have been widely used for targeted drug delivery therapies for treating various inflammatory and tumor-related diseases. Compared to other drug-loaded treatments, drug-loaded platelets have better targeting, superior biocompatibility, and lower immunogenicity. Drug-loaded platelet therapies include platelet membrane coating, platelet engineering, and biomimetic platelets. Recent studies have indicated that platelet extracellular vesicles (PEVs) may have more advantages compared with traditional drug-loaded platelets. PEVs are the most abundant vesicles in the blood and exhibit many of the functional characteristics of platelets. Notably, PEVs have excellent biological efficacy, which facilitates the therapeutic benefits of targeted drug delivery. This article provides a summary of platelet and PEVs biology and discusses their relationships with diseases. In addition, we describe the preparation, drug-loaded methods, and specific advantages of platelets and PEVs targeted drug delivery therapies for treating inflammation and tumors. We summarize the hot spots analysis of scientific articles on PEVs and provide a research trend, which aims to give a unique insight into the development of PEVs research focus.